2010
DOI: 10.1603/ec09364
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Insecticides Used for Control of <I>Piezodorus guildinii</I> (Heteroptera: Pentatomidae) in the United States and Brazil

Abstract: Limited information exists on the insecticide susceptibility of redbanded stink bug, Piezodorus guildinii (Westwood) (Heteroptera: Pentatomidae), despite its impact on soybean, Glycine max (L.) Merr., production in Brazil and the United States. Therefore, this study set out to 1) determine baseline levels of susceptibility to currently recommended pesticides using topical and vial bioassays, 2) determine the levels of esterase activity in populations in the United States and Brazil, and 3) compare control amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 12 publications
0
32
0
1
Order By: Relevance
“…This study confirms reports from agricultural consultants and producers that the redbanded stink bug is less susceptible than the southern green stink bug to numerous insecticides. In field studies from 2003 to 2006, Baur et al (2010) reported redbanded stink bug control of 81 and 69% for acephate and methyl parathion, respectively. In the current study, control by acephate (86%) was similar but slightly greater than for methyl parathion (82%).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study confirms reports from agricultural consultants and producers that the redbanded stink bug is less susceptible than the southern green stink bug to numerous insecticides. In field studies from 2003 to 2006, Baur et al (2010) reported redbanded stink bug control of 81 and 69% for acephate and methyl parathion, respectively. In the current study, control by acephate (86%) was similar but slightly greater than for methyl parathion (82%).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, control by acephate (86%) was similar but slightly greater than for methyl parathion (82%). This may be attributed to the use of field rates approximately 25% greater than rates used by Baur et al (2010). Baur et al (2010) reported that control of redbanded stink bugs with pyrethroids (bifenthrin, cyfluthrin, gamma-cyhalothrin, lambda-cyhalothrin, and zetacypermethrin) ranged from 52 to 80%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations